Quality Management in Turkish Public Management: Challenges and Benefits - Karasoy, Hasan Alpay (European Scientific Journal, ESJ, 2018)
From the late 1970â€™s onwards, traditional public administration was criticized because it does not meet the needs of developing and changing new world. Following this critique, a new approach to public administration was proposed under the name of New Public Management. The development of new public management changed the concept of the public service. Accountable, transparent, effective, and efficient services have become the basic principles of management. On the other hand, the term â€œqualityâ€ has also gained popularity in public administration. In this sense, Total Quality Management (TQM) was adopted to develop quality systems in public administration worldwide. Turkey has also adopted that system. In this study, the situation assessment of TQM process in Turkey was made through the presentation of strengths and weaknesses. The literature search is conducted to achieve this aim and it is obtained from the research that since quality management cannot be fully realized, there are some deficiencies in practice and in regulatory. In this context the regulatory process needs to be revised specially in terms of evaluating and auditing.